Seasonal Analysis of Total Premiums Written of the Motor Third Party Liability Insurance in The Czech Republic In Years 2000 - 2016 from the Marketing Perspective - Eisenhammerova, Monika; Chocholac, Jan (Communications - Scientific letters of the University of Zilina, 2017)
The insurance sector is in many ways unique, because insurance companies must use specific marketing tools to satisfy their customers and insurance companies have with customer’s long-term relationships. Insurance companies must continuously monitor the insurance market, especially type of demand for insurance products and customer requirements. The number of registered vehicles in the Czech Republic is annually increasing, which causes an increase of total premiums written of the motor third party liability insurance and insurance companies must monitor this insurance product and analyse demand for it. The aim of this article is to analyse the seasonality of total premiums written of motor third party liability insurance in the Czech Republic in years 2000 - 2016.